Determine supporting features for mobile application of NUSANTARA - Dana I. Sensuse; Ika Arthalia Wulandari; Erzi Hidayat; Elin Cahyaningsih; Pristi Sukmasetya; Wina Permana Sari (IAES Indonesia Section, 2018)
This paper is a continuation of previous research focusing on the development of a model of knowledge management system for civil servant from three ministries in Indonesia (KEMENPAN&RB, BKN, and LAN). From previous study obtain a knowledge management model which is Government Human Capital Knowledge Management of Republic of Indonesia (NUSANTARA). Implementation of this model is conducted with web system, further development of this system still provides constraints from several sides in providing more optimal service against users requirements as well as limited accessibility and responsiveness. This paper aims to explore the supporting features that will be used to integrate pre- existing systems that build mobile knowledge management applications. Data were collected by interview from each related institution. The CommonKADS method is chosen as a technique to explore the problems and knowledge of each organization. SMAPA method is used to validate the result from the experts and end users. Results of this work are produced seven recommended supporting features there are vision and mission view, activity notification, group discussion, search repository, upload document and document activities log.